1970
DOI: 10.1161/01.cir.42.4.567
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic Findings in 123 Patients with Acute Myocardial Infarction on Admission

Abstract: Hemodynamic and clinical evaluations of 123 patients with acute myocardial infarction were performed during the first hour of admission to the hospital. In the 123 patients, the right atrial pressure was less than 10 mm Hg in 49 patients, the right atrial oxygen saturation was less than 70% in 97 patients, the arteriovenous oxygen difference was greater than 5.0 vol% in 78 patients. The arterial Po2 was less than 90 mm Hg in 101 of 107 patients who could be evaluated while breathing room air. The cardiac index… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
3

Year Published

1972
1972
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(14 citation statements)
references
References 25 publications
0
11
0
3
Order By: Relevance
“…These data under score the fact that subsequent left ventricular dysfunction in individual patients cannot always be predicted by the site or type of myocardial infarc tion. Rather, total infarct size is most likely the best predictor of subsequent left ventricular performance and an important indicator of overall prognosis [81-Several investigators [11][12][13][14][15] have studied left ventricular function fol lowing acute myocardial infarction in man, but there have been few studies documenting actual changes in left ventricular performance prior to and following infarction. Stewart et al…”
Section: Discussionmentioning
confidence: 99%
“…These data under score the fact that subsequent left ventricular dysfunction in individual patients cannot always be predicted by the site or type of myocardial infarc tion. Rather, total infarct size is most likely the best predictor of subsequent left ventricular performance and an important indicator of overall prognosis [81-Several investigators [11][12][13][14][15] have studied left ventricular function fol lowing acute myocardial infarction in man, but there have been few studies documenting actual changes in left ventricular performance prior to and following infarction. Stewart et al…”
Section: Discussionmentioning
confidence: 99%
“…In three patients (9, 11, and 12), however, the ventricle responded to reduction in LVEDP with a rise in stroke volume. In six patients (4,5,7,8,10, and 11), similar volume manipulations were carried out in the follow-up studies. When cardiac function curves from different studies in the same patient were compared, no consistent pattern emerged.…”
Section: Materials and Methods Materialsmentioning
confidence: 99%
“…[1][2][3][4][5] Changes in cardiac output and systemic vascular resistance during the first week after infarction also have been reported.5 6 Recent studies in this laboratory using a bedside technic for left ventricular catheterization7 have revealed that left ventricular function is almost invariably impaired after acute myocardial infarction even in the absence of clinical signs of left ventricular failure. However, it is not known whether this abnormality is transient and reversible or persists during convalescence.…”
Section: )Lumementioning
confidence: 99%
“…Because of the differing methods of estimating CO , we subdivided our results into studies that evaluated the capacity of physicians to estimate CO ( n  = 17; Table 2) [13–18,5261,62 ▪▪ ] and studies that constructed clinical profiles based on multiple variables ( n  = 3) or a multivariable model ( n  = 1) to correlate clinical examination findings with CO (Table 3) [6366]. Furthermore, we could calculate the diagnostic test accuracy for physician's estimation of low CO in nine studies (Table 2).…”
Section: Multivariable Studiesmentioning
confidence: 99%